Pengetahuan Dan Kesadaran Masyarakat Dalam Kepatuhan Membayar Pajak Bumi Dan Bangunan Di Dusun Kalipanggang Desa Candirejo Tuntang - Kusumaningrum, Feny Retno (Jurnal Akuntansi dan Pajak, 2020)
The tax compliance of property tax in Candirejo Tuntang village especially Kalipanggang hamlet has not reached its target that has been set, the percentage rate of property tax.in these last five years still below the target which is 80% with 141 taxpayers. This percentage can be seen in 2015 which shows a figure 56,16 %, then in 2016 with the percentage 60,26 % , and then in 2017 as much as 66,00 % and in the year 2018 as much as 70,15 %. The percentage increase from 2015 until 2018, but in 2019 the percentage rate is decrease to 64,96 %.The method of this research is qualitative descriptive, while the purpose is to measure the depth of public knowledge and awareness in hamlet Kalipanggang to pay the property tax. Data collection techniques in this research are: observation, interview, and documentation method, then the technical analysis are: consisting of data reduction, presentation of data, and the conclusion. The result of this research shows that mostly taxpayers don't really understand yet about the rules and the purpose of property tax so they need to re-explain, taxpayers only know the sanction of a fine for it’s been written in SPPT (a letter of tax notification). The awareness of taxpayers is so low because they let their tax arrear for years. Most of the taxpayers prioritize the primary and secondary needs than pay their tax, it's also because the small amount of income taxpayers. The things needed to raise the awareness of paying property tax are to improve the public services, especially in property tax and provide an explanation, which taxpayers have been given information and knowledge about the role and benefit of property tax so people can raise the awareness in order to do their duty tax.